PUBLIC-PRIVATE PARTNERSHIPS IN FINANCING THE GREEN TRANSITION (TECHNICAL SCIENCE RESEARCH IN UZBEKISTAN, 2025)
The transition to a green economy requires substantial investment in clean technologies, renewable energy, and climate-resilient infrastructure. Governments alone cannot shoulder this burden; hence, Public-Private Partnerships (PPPs) have emerged as a vital mechanism for mobilizing additional capital and expertise. This paper explores how PPPs can accelerate the green transition by aligning public policy objectives with private sector innovation and financial capacity